2020
DOI: 10.5272/jimab.2020262.3168
|View full text |Cite
|
Sign up to set email alerts
|

Shade Guides Used in the Dental Practice

Abstract: The aim of the article is to present a narrative review of the literature related to the different shade guides available for dental practitioners.A literature search was performed in the online databases -PubMed, Science Direct, MedLine and GoogleScholar with the following keywords -shade guide, shade matching, dental, dentistry. Furthermore, a hand search, including "grey" literature and printed resources available to the authors, was conducted. More than 2100 unique articles, including the selected keywords… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Oral tissues should be at the eye level; this is how the most color-sensitive part of the retina is used. The time for optimal color determination is about 15-20 s. If it takes longer to determine the color, it is recommended to shift the gaze to another surface (preferably gray) [25]. Squinting also helps determine color saturation.…”
Section: Visual Methods For Color Determinationmentioning
confidence: 99%
“…Oral tissues should be at the eye level; this is how the most color-sensitive part of the retina is used. The time for optimal color determination is about 15-20 s. If it takes longer to determine the color, it is recommended to shift the gaze to another surface (preferably gray) [25]. Squinting also helps determine color saturation.…”
Section: Visual Methods For Color Determinationmentioning
confidence: 99%
“…Finally, the color tone (hue) is determined. This system is used in the visual determination of color [25].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…To identify hues, the Chromascop numbering system is employed. Depending on the color, it is divided into categories (100 = white, 200 = yellow, 300 = orange, 400 = gray, 500 = brown) and within the groups, as chroma increases from 10 to 40 [35] It has been observed that a number of improvements have been developed for the Vita 3D Master shade guide, as compared to Vita Classical:…”
Section: Chromascop Shade Guidementioning
confidence: 99%
“…To identify hues, the Chromascop numbering system is employed. Depending on the color, it is divided into categories (100 = white, 200 = yellow, 300 = orange, 400 = gray, 500 = brown) and within the groups, as chroma increases from 10 to 40 [35]…”
Section: Chromascop Shade Guidementioning
confidence: 99%